A heart of blood and ashes - Vane, Milla (A gathering of dragons., 2020)
Vowing to avenge his parents' murders even if it costs him the Parsathean crown, barbarian warrior Maddek kidnaps the king's daughter who shocks him by proposing a marriage to unite them in their goals and destroy her father.